PERAN LAKI-LAKI SINGLE PARENT DALAM KELUARGA DI NAGARI KURNIA KOTO SALAK, KECAMATAN SUNGAI RUMBAI,KABUPATEN DHARMASRAYA - Arianti, Willy; Erningsih, Erningsih; Yatim, Yenita (Jurnal Intervensi Sosial dan Pembangunan, 2024)
Single parents are people who carry out their duties as parents (father or mother) alone, because they have lost/separated from their partner. So that the role carried out in the family becomes double. Especially for a husband who was abandoned by his wife, due to death or divorce. This study aims to describe the Role of Single parent Men in the Family in Nagari Kurnia Koto Salak, Sungai Rumbai District, Dharmasraya Regency. The theory used in this study is Biddle Thomas' role theory. This study used a qualitative research method with a descriptive research type. Withdrawal of informants was carried out using a purposive sampling technique. The data collection method in this study began with observation, interviews, and document study. Data analysis techniques in research can be carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that there were 3 roles of single parent males in the family, namely 1). Single parent Men as Household Managers 2). The Role of Single parent Men as Educators and 3). The Role of Single parent Men in Society.